THE IMPACT OF BIOMECHANICAL FACTORS ON ENHANCING SPORTS PERFORMANCE AND INJURY PREVENTION - Sajjad Hassan Maktoof Jabara; Jassim Jabara Jassim Ati (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Biomechanics is an important part of modern sports science because it looks at the mechanical rules that regulate how people move to improve performance and avoid injury. As evidence-based training becomes more important, it's important to know how biomechanical aspects like movement patterns, joint mechanics, and muscle activity affect safety, efficiency, and endurance in different sports. Objectives. This study seeks to examine the influence of biomechanical parameters on enhancing performance outcomes and mitigating the risk of sports-related injuries. Method. Utilizing a descriptive-analytical methodology, data were gathered from prior experimental investigations and performance reports in sports, swimming, and cycling to assess biomechanical interventions. Results. The findings indicate that biomechanical modifications markedly enhance athletic efficiency: optimizing platform length and stride length enhances running performance by 8%, altering swimming technique increases propulsion efficiency by 5%, and achieving optimal cycling posture boosts power output by 10% while decreasing air resistance by 7–10%. Moreover, biomechanics-based training programs markedly diminished the occurrence of anterior cruciate ligament (ACL) injuries among female athletes. Conclusion. The results indicate that incorporating biomechanical principles into training and performance assessment can lead to quantifiable enhancements in technique and injury prevention. In summary, biomechanics connects scientific knowledge with athletic practice, making it possible to create evidence-based therapies that improve performance and keep athletes healthy. This study adds to the body of research by emphasizing the significance of biomechanical analysis as a basis for enduring and secure sports performance.